Modelo de seleção de critérios para avaliação de desempenho ESG - Garais, Eloisa da Silva (2023)
Research indicates that the adoption of new business models, focused on environmentally and socially responsible products, can generate greater economic value. These models allow the exploration of new markets, driven by the demand for products and services that are environmentally friendly, sustainable and socially responsible, resulting in the creation of additional value. Non-financial data, such as environmental, sustainability and corporate social responsibility reporting, is becoming increasingly accessible and available. In this context, the concept of Environment, Social and Governance (ESG) has gained prominence in new business models. There is growing interest from investors, shareholders, government and regulatory authorities in relation to ESG and its implications. This work aimed to propose a criteria selection model for evaluating ESG performance, considering user preferences, as well as providing a repository of criteria, with a generic nature, that can be used in the most varied types of business segments or research. academics. The main methods used were bibliographic search, to build the criteria repository, application of the AHP (Analytic Hierarchy Process) and 2-tuple multi-criteria decision methods, to process information obtained in personal interviews, group meetings and forms answered in a online, carried out during an application case promoted in a medium-sized sawmill, located in the center-south of the State of Paraná. From the bibliographic search, based on literary and non-literary sources, such as regulatory frameworks and ESG reports from large corporations, it was possible to create a repository with one hundred and five environmental, social and governance criteria, which were used in the application case. The results of the application case made it possible to visualize an ordering of the criteria selected by the decision-makers, identifying the most relevant criteria in each group. Although no previous studies were found for direct comparison, the results contribute to the study area, providing a criteria selection model for evaluating ESG performance adaptable to different segments and a repository of general ESG criteria. Limitations were found, such as, for example, the need to adapt the model according to the application segment, but the results of the application case are aligned with the organization's objectives. Key contributions include the proposed model, criteria repository, and opening up future research directions. In short, this research provided a model for selecting ESG criteria, which can be used in ESG performance reports and highlighted its applicability in different segments, allowing improvements and opening paths for future studies, based on the model.